Critical Race Theory and Caring as Channels for Transcending Borders between an African American Professor and Her Latina/o Students - Koonce, Jacqueline B. (International Journal of Multicultural Education, 2018)
This reflective essay uncovers ways in which critical race theory and caring are key to crossing racial, cultural, and linguistic borders between professors and their students. Many scholars have noted how critical reflection relates to effective teaching, especially when taking into account student learning. Reflecting upon archival data and participant observation, the author describes, through various stories, how she uses critical race theory and caring to connect with her students in spite of their differences. The author also provides examples of how her students reciprocate her care in extravagant ways.